Application of Oxygen Therapy and Deep Dhiaphragmatic Breathing to Overcome Shortness of Breath with Acute Decompensated Heart Failure - Ainun Annisha; Haeril Amir; Nur Wahidah; Nurhawa Karepesina; Rahmat Hidayat (An Idea Health Journal, 2023)
Acute heart failure is a term used to indicate a change or event that is very fast where this is characterized by signs or symptoms of heart failure itself so that it can threaten life and life and this needs to be treated immediately The prevalence of heart failure continues to increase every year , The American Heart Association Statistics Update 2021 estimates the prevalence of heart failure to be 6 million of which 1.8 % of the total population of the United States and Canada is 1.5 % to 1.9 % of the population and in Europe 1 % to 2 % (Roger, 2021 ). On the Asian continent, it occupies the highest place due to heart disease deaths with a total of 2,769,000 people. Indonesia ranks second in Southeast Asia with a total of 371 thousand people (WHO, 2017). The purpose of this study was to find out the description of the application of oxygen therapy and Deep Dhiafragmatic Breathing On Mrs. "S" With Problems Acute Decompensated Heart Failure in room Cardiovaskular Care Unit (CVCU) of the Laburan Baji General Hospital, Makassar. The results of the study showed that there was a decrease in shortness of breath after being given oxygen therapy intervention and deep dhiafragma breathing to the client for 3 days of treatment. Where on the first day the respiration rate was 28x/minute and SpO2 was 95%, on the second day the respiration rate was 26x/minute and 97% SpO2, the third day the respiration rate was 24x/minute and SpO2 was 98%. Which indicates amchange in respiratory frequency before and after being given nursing interventions.